Technological innovation generating economic results - Thursby, Marie (Advances in the study of entrepreneurship, innovation, and economic growth, 2016)
We are pleased to present this 2nd edition of Technological Innovation, originally published in 2008. Profiting from technological innovation is a key strategic challenge in technology-intensive industries because it requires not only scientific and engineering expertise, but also an understanding of how business and legal factors facilitate commercialization. This volume presents a multidisciplinary view of issues in technology commercialization and entrepreneurship. Chapters cover commercializing inventions in the context of the legal system and the complementary assets needed; the benefits and liabilities associated with multidisciplinary commercialization teams, including a basic guide to patents and designs; elements of strategy, including industry analysis and strategy, marketing strategy, and alliances; and finally, the financial issues in commercialization.